Ultrasonography of peripheral nerve tumours: a case series - Podnar Simon (Radiology and Oncology, 2023)
Peripheral nerve tumours (PNTs) are rare, but important cause of peripheral nerve dysfunction. The aim of the study was to present a series of consecutive patients with PNTs evaluated in authors’ ultrasonography (US) practice.